Kajian Kinerja Penatua Pemuda Dalam Membangun Kesadaran Pemuda Untuk Beribadah Di Jemaat GMIM Efarata Wusa Wilayah Mapanget IV - Wagania, Stevanoch M. (Educatio Christi, 2021)
Worship is something that is very important for Christians, especially among today's young people. This article aims to discuss the performance or role of Youth Elders in building youth awareness in worshiping in the "GMIM Efrata Wusa" congregation. The question is whether the performance and role of a youth Elder influences the diligence and activeness of youth members in worship and youth make worship not just an obligation. as Christians but rather as a part of their lives. The method used by researchers in this research is a qualitative method by collecting library data, both books and conducting field research. Through this discussion the author offers a new perspective in Biblical theology regarding the role of Youth Elders who greatly influence the lives of young people in their active worship as church youth. My thesis is that Youth Elders are Special Servants who have a big responsibility in building the spirituality of church youth so that youth truly become responsible church members in terms of worship. This article ends with a conclusion.